PENGARUH KUALIFIKASI HASIL SELEKSI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI GRAND ROCKY HOTEL BUKITTINGGI - FERI FERDIAN; Ira Meirina; Fitri Afriana (JURNAL PENDIDIKAN DAN KELUARGA, 2017)
The purpose of this research is to examine the influence between the qualification of selection toward work productivity employee in Grand Rocky Hotel Bukittinggi. The Type of research is clausal assosiative.The sampling technique is probability sampling by using proportionate stratified random sampling. Sample in this research are amounted to 53 people. Data collecting using questionnaires based on likert scale that has been tested of validity and reliability. Based on the result of thereresearch concluded that in general about qualification of selection in Grand Rocky Hotel Bukittinggi is als good 38,62 %. Work productivity employee in Grand Rocky Hotel Bukittinggi is also good 66,7 %. The result also indicate that are significant influence between qualification of selection and work productivity in Grand Rocky Hotel Bukittinggi is 51,2% and 48,8% another factor on a 0,000 < 0,05 significant.